Log in to add a comment

## Answers

5a² - 3b² + 16b² - 3a² - 11a² - 9b²

= 2a² +13b² -11a² - 9b²

= -9a² +4b²

= 2a² +13b² -11a² - 9b²

= -9a² +4b²

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

So we add

5a² - 3b² + 16b² - 3a² - 11a² - 9b²

so simply add as if doing adding and subtraction simply with the numbers but just do b with b and a with a

= -6a² +13b² -3a² - 9b²

= -9a² +4b²

5a² - 3b² + 16b² - 3a² - 11a² - 9b²

so simply add as if doing adding and subtraction simply with the numbers but just do b with b and a with a

= -6a² +13b² -3a² - 9b²

= -9a² +4b²